1999
DOI: 10.1093/carcin/20.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of induction of DNA adducts, cell proliferation and gene mutations in the liver of Muta™Mice treated with 5,9-dimethyldibenzo[c,g]carbazole

Abstract: 5,9-Dimethyldibenzo[c,g]carbazole (DMDBC) is a synthetic derivative of the environmental pollutant 7H-dibenzo[c,g]carbazole. DMDBC is a potent genotoxic carcinogen specific for mouse liver. Using the MutaMouse lacZ transgenic mouse model and a positive selection assay, we measured lacZ mutant frequency (MF) in the liver 28 days after a single s.c. administration of DMDBC at 3, 10, 30, 90 or 180 mg/kg. MF remained low at 3 and 10 mg/kg, but increased markedly from 30 mg/kg onwards. To investigate the reason for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
5
13
0
Order By: Relevance
“…The detection of apoptosis at earlier applications was the consequence of using a more sensitive technique (TUNEL) for detecting apoptotic nuclei, and indicated that the critical adduct level from which they induced toxicity could be lower. In our study, large interanimal variations were observed in the apoptotic index of the groups that received a high number of applications of 7H-DBC, and this fact is in agreement with the results of Tombolan et al (1999a) with respect to the variations of the mutation frequency in liver from mice treated with high doses of 7H-DBC. In accordance with our previous results, the apoptosis index revealed that DBC toxicity increased with the number of applications and was higher in periportal areas.…”
Section: Immunohistochemical Analysissupporting
confidence: 91%
“…The detection of apoptosis at earlier applications was the consequence of using a more sensitive technique (TUNEL) for detecting apoptotic nuclei, and indicated that the critical adduct level from which they induced toxicity could be lower. In our study, large interanimal variations were observed in the apoptotic index of the groups that received a high number of applications of 7H-DBC, and this fact is in agreement with the results of Tombolan et al (1999a) with respect to the variations of the mutation frequency in liver from mice treated with high doses of 7H-DBC. In accordance with our previous results, the apoptosis index revealed that DBC toxicity increased with the number of applications and was higher in periportal areas.…”
Section: Immunohistochemical Analysissupporting
confidence: 91%
“…One of the potential mechanisms involved could be the disruption of cell cycle control leading to enhanced cell proliferation, which may potentiate genotoxic effects of PAHs and contribute to tumour promotion (Tombolan et al, 1999;Bishop et al, 2001). We have previously used contact-inhibited WB-F344 cells as a model to study impact of PAHs on cell proliferation, and we have found that the proliferative effects of PAHs in this cell line are AhR-dependent (Chramostová et al, 2004;Andrysík et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…1), because their presence is highly dependent on diet, age, and gender [Lu et al, 1990;Patel et al, 1998]. A recent study using other transgenic mice with a reporter gene (Muta™Mouse) showed a relationship between adduct formation and mutant induction following a 5,9-dimethyldibenzo[c, g]carbazole exposure [Tombolan et al, 1999]. Nevertheless, in this study a linear relationship between the number of detected adducts and the mutation induction factor was evidenced.…”
Section: -Methylcholanthrene and Dna Adductionmentioning
confidence: 59%